Facilitating collective action - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Through collective action, forest users, fishers, irrigators, herders, and other rural producers improve and sustain resources vital for their lives. In cases where it has weakened or seems absent, citizens, non-government organizations (NGOs), and government agencies can work to stimulate, strengthen, or sustain collective action.